Detection of episomal banana streak badnavirus (BSV) in Philippine Musa germplasm collection by immunocapture-polymerase chain reaction (IC-PCR) - Dinglasan, Eric G. (Transactions of the National Academy of Science and Technology, 2011)
Banana streak badnavirus (BSV), one of the five described viruses infecting banana (Musa sp), is currently being considered a serious threat and major constraint to Musa genetic improvement and germplasm movement. The virus occurs as non-infectious endogenous, wherein viral sequence is incorporated naturally on Musa genome, or infectious episomal, which can originate through activation from the endogenous sequences triggered by abiotic stress like tissue culture and drought condition. Accurate detection method must be developed/adapted and used to index the existing germplasm for the presence of episomal BSV. Virus detection was done using Immunocapture-Polymerase Chain Reaction (IC-PCR), which specifically detects episomal virus. Using purified BSV antibody and BSVF1/R1 primers, IC-PCR showed that 18 out of the 22 cultivars tested (82%) gave an amplification product of 220bp indicating the presence of episomal virus. Only 4 cultivars (18%) were negative to BSV. It was noted that all the leaf samples collected from the germplasm came from plants with no typical symptoms of virus infection. Based on the TR, it is very important to use an accurate and effective detection method to determine the presence of episomal BSV in the germplasm collection as part of tight integrated management measures.